2021
DOI: 10.3390/cells10030640
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium (II)-Induced Oxidative Stress Results in Replication Stress and Epigenetic Modifications in Root Meristem Cell Nuclei of Vicia faba

Abstract: Among heavy metals, cadmium is considered one of the most toxic and dangerous environmental factors, contributing to stress by disturbing the delicate balance between production and scavenging of reactive oxygen species (ROS). To explore possible relationships and linkages between Cd(II)-induced oxidative stress and the consequent damage at the genomic level (followed by DNA replication stress), root apical meristem (RAM) cells in broad bean (V. faba) seedlings exposed to CdCl2 treatment and to post-cadmium re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…After 72 h, plants with roots approximately 2.5 cm long were placed in distilled water (control) and 150 µM CdCl 2 solution. The concentration of CdCl 2 was selected based on the available literature data, e.g., [ 44 , 45 ], based on the results obtained in a series of preliminary tests and applied in earlier studies [ 31 ]. Cultures were aerated by gentle rotation of Petri dishes in a water-bath shaker (60 r.p.m.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 72 h, plants with roots approximately 2.5 cm long were placed in distilled water (control) and 150 µM CdCl 2 solution. The concentration of CdCl 2 was selected based on the available literature data, e.g., [ 44 , 45 ], based on the results obtained in a series of preliminary tests and applied in earlier studies [ 31 ]. Cultures were aerated by gentle rotation of Petri dishes in a water-bath shaker (60 r.p.m.…”
Section: Methodsmentioning
confidence: 99%
“…RS triggers a set of cellular signaling mechanisms to single and double stranded DNA damage sites at stalled or slowed down replication forks. Using γ-H2AX immunofluorescence labeling, our previous experiments [ 31 ] showed an increased number of visible γ-H2AX foci in V. faba cells exposed to 24 h incubation with CdCl 2 and a decreased level of H2AX phosphorylation in the control root cells (after post-cadmium recovery in water). While γ-H2AX is primarily a DSBs marker, ample evidence points to a more general role of γ-H2AX during RS, both in inhibiting replication forks in the absence of DSBs and in repairing collapsed replication forks [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular level, Cd toxicity can be explained by its ability to react with the sulfhydryl groups of proteins, replacement of some essential elements at the active sites of enzymes, and replacement of magnesium in both chlorophyll a and b [4,6]. Although Cd is not a redox-active metal, it can induce oxidative stress, possibly by interfering with an antioxidant defense, by increasing nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity, or by disrupting the electron transport chain [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, such a model study has not been replicated in plants and such a knowledge gap demands exploration by crop scientists and plant biotechnologists for future perspectives. Additionally, Zabka et al [34] used apical root meristem in V. faba seedlings exposed to CdCl 2 to monitor the epigenetic changes in transcription nucleosome assembly during the S-phase of the cell cycle. The study revealed cellular responses to Cd toxicity are interlinked with biochemical reactions through the generation of ROS and DNA-damage-induced replication stress.…”
Section: Chromatin Remodeling and The Effect Of Cadmium Stress In Plantsmentioning
confidence: 99%
“…Zabka et al [34], explored the possible relationships and linkages between Cd (II)induced oxidative stress and the consequent damage at the genomic level of in the V. faba seedlings exposed to Cd treatment and to post stress recovery water incubations. Exposure to Cd toxicity therefore leads to two types of consequent Cd-induced secondary stress conditions, including oxidative stress, by which reactive oxygen species (ROS) played an important part in producing disorder at the genomic DNA level eventually leading to replication stress.…”
Section: The Effects Of Cadmium On Histone Acetylationmentioning
confidence: 99%